Analisis Dan Pemodelan Motor Induksi Kapasitor Permanen Dengan Rangkaian Ekivalen Invers Γ - Elfi Martina; Amir Hamzah; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Analysis and modelling of induction motor of permanent capacitor have been done in this paper. With specifications 30 Volt, 100 Watt, 6 pole, 50 Hz, 1000 rpm. At this writing the equivalent circuit Г inverse form by simplifying the parameters which determine the stator reactance leak is not the sameas leaking rotor reactance. So that the determination of the parameters can be done more thoroughly. Modeling transient permanent capacitor induction motor has been done using MATLAB- Simulink. In this research, the percentage of permanent capacitor induction motor error burden from direct test results and simulation results that the initial voltage on the primary winding by 3.46%, the initial voltage on the auxiliary winding of 8.896%, stable voltage on the auxiliary winding by 9.89%, currents starting on auxiliary winding by 19.97% and stable current on auxiliary winding by 21.44%. From the shape of the voltage waveform generated change, the results of experimental approaches the simulation calculation results on the primary winding and the auxiliary winding thus obtained avalid analysis.Keywords : Permanent capacitor induction motor, induction motor modeling using inverse Γ equivalent circuit, Simulink - Matlab.